The Potential Use of Anthocyanin in Butterfly Pea (Clinoteria ternatea) Petals as Colorimetric Indicator in Intelligent Food Packaging Article - Siti Radhiah Omar; Ahmad Adham Noh; Ahmad Naim Rohaizan (USIM Press, 2024)
Vol. 8 No. 1 (2022)